Gebrakan Bank Aladin Syariah dalam Digitalisasi Ekonomi Syariah dan Perbankan Modern - Dea Ananda (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
The development of the sharia economy in Indonesia has experienced rapid progress in recent decades, one of which is influenced by the active role of sharia financial institutions, especially sharia banks. Bank Aladin Syariah, which was born with a digital concept, is committed to providing sharia-based financial solutions that are easily accessible and efficient. This study aims to analyze the contribution of Bank Aladin Syariah to the development of the sharia economy in Indonesia through a literature review approach. The results of the study show that Bank Aladin Syariah not only provides innovative products in digital banking, but also plays a role in increasing financial inclusion, sharia financial literacy, and empowering MSMEs in Indonesia. However, challenges such as competition with large sharia banks and the low public understanding of sharia banking are still major issues that need attention.